If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + (3 + b) = 0 Remove parenthesis around (3 + b) 6 + 3 + b = 0 Combine like terms: 6 + 3 = 9 9 + b = 0 Solving 9 + b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + b = 0 + -9 Combine like terms: 9 + -9 = 0 0 + b = 0 + -9 b = 0 + -9 Combine like terms: 0 + -9 = -9 b = -9 Simplifying b = -9
| 4(4-2x)=24-4x | | 5x+2y+2=80 | | 2*2-18x=0 | | 5+2n-3n=8 | | A=zm+zform | | -8x-62=64-2x | | x+3x-2=78 | | 128=96t-16t^2 | | 4y+8=4y-9 | | -8=9v-5+32 | | s-3=5-2 | | 10=5(x+3) | | 3x+18=x+32 | | 5w+8-w=7w-2(w-4) | | 1-3=5-1 | | 7m-3=9m+6-m | | -85+3x=83-9x | | (5x-3)+(n+9)=24 | | X^3+13x^2=0 | | 6y+4=6y-9 | | 16(z+3)=4(z-9) | | (2x-4)(x+3)= | | 2a-4b=58 | | -a+5=5a+5 | | 3x-7=-3 | | F(5)=20x+11 | | 4x^3+8x^2+3x+6=0 | | q-rb=15a | | 2x+12i=3y+2yi | | 12p=p+24+p | | 18x^2+45x+15=-10 | | 2w+9=-3 |